Tropical temperature trends in Atmospheric General Circulation Model simulations and the impact of uncertainties in observed SSTs. Issue 23 (11th December 2014) - Flannaghan, T. J.; Fueglistaler, S.; Held, I. M.; Po‐Chedley, S.; Wyman, B.; Zhao, M.
Abstract The comparison of trends in various climate indices in observations and models is of fundamental importance for judging the credibility of climate projections. Tropical tropospheric temperature trends have attracted particular attention as this comparison may suggest a model deficiency. One can think of this problem as composed of two parts: one focused on tropical surface temperature trends and the associated issues related to forcing, feedbacks, and ocean heat uptake and a second part focusing on connections between surface and tropospheric temperatures and the vertical profile of trends in temperature. Here we focus on the atmospheric component of the problem. We show that two ensembles of Geophysical Fluid Dynamics Laboratory HiRAM model runs (similar results are shown for National Center for Atmospheric Research's CAM4 model) with different commonly used prescribed sea surface temperatures (SSTs), namely, the HadISST1 and "Hurrell" data sets, have a difference in upper tropical tropospheric temperature trends (∼0.1 K/decade at 300 hPa for the period 1984–2008) that is about a factor 3 larger than expected from moist adiabatic scaling of the tropical average SST trend difference. We show that this surprisingly large discrepancy in temperature trends is a consequence of SST trend differences being largest in regions of deep convection. Further, trends, and the degree of agreement with observations, not only depend on SST data set and the particular atmospheric temperature data set but also on the period chosen for comparison. Due to the large impact on atmospheric temperatures, these systematic uncertainties in SSTs need to be resolved before the fidelity of climate models' tropical temperature trend profiles can be assessed.